MiR‐150 is associated with poor prognosis in esophageal squamous cell carcinoma via targeting the EMT inducer ZEB1. Issue 1 (8th November 2012) - Yokobori, Takehiko; Suzuki, Shigemasa; Tanaka, Naritaka; Inose, Takanori; Sohda, Makoto; Sano, Akihiko; Sakai, Makoto; Nakajima, Masanobu; Miyazaki, Tatsuya; Kato, Hiroyuki; Kuwano, Hiroyuki
<x xml:space="preserve">Abstract</x> The association of microRNAs (miRs) with cancer progression has been established in many cancers including esophageal squamous cell carcinoma (ESCC). A public microarray database showed that the expression of miR‐150 was lower in ESCC than in normal esophageal mucosa. Here, we focused on ZEB1, epithelial‐mesenchymal‐transition (EMT)‐inducer, as a target gene of miR‐150 based on in silico predictions. The purpose of this study was to clarify the clinicopathological significance of miR‐150 in ESCC, and to investigate miR‐150′s EMT‐regulatory ability. Quantitative RT‐PCR was used to evaluate miR‐150 expression in 108 curative resected ESCC samples to determine the clinicopathological significance. Moreover, we examined the in vitro and in vivo function of miR‐150 via degradation of ZEB1. MiR‐150 expression was significantly lower in cancer tissues compared to adjacent non‐cancerous tissues (P < 0.001). Low expression of miR‐150 in ESCC contributed to malignant potential, such as tumor depth, lymph node metastasis, lymphatic invasion, venous invasion, clinical staging, and poor prognosis (P < 0.05). In vitro assays showed that EMT‐inducer‐ZEB1 is a new direct target of miR‐150. Moreover, miR‐150 induced MET‐like changes in TE‐8 cells through ZEB1 degradation (e.g., E‐cadherin expression, vimentin repression, epithelial morphology, and suppression of migration ability), and significantly inhibited tumorigenicity and tumor growth in a mouse xenograft model. Analysis of the regulation of ZEB1 by miR‐150 could provide new insights into preventing metastasis and also suggests novel targeted therapeutic strategies in ESCC. (Cancer Sci 2013; 104: 48–54)